Workplace aggression in the healthcare sector: a scoping review to facilitate the development and evaluation of effective de-escalation training programs - Corsi, Martina; Perretta, Salvio; Marino, Riccardo; Doda, Aleksandra; Buselli, Rodolfo; Foddis, Rudy (International Journal of Occupational Safety and Health, 2024)
Introduction: Workplace aggression is a challenge for preventive and occupational medicine and aggression management training is fundamental to any workplace violence prevention strategy. Despite the increasing interest that has been recently devoted to the importance of prevention of aggressive behaviors, international literature on the topic is huge but heterogeneous. Methods: The authors tried to to analyze literature regarding this issue with the future goal of finalizing a de-escalation training course for healthcare workers, alongside a procedure for evaluating the effectiveness of the course that takes into account evidence synthesis. Results: Although in recent years several studies have proposed different theoretical models of escalation of aggression and de-escalation techniques, what emerged is that no model can possibly account for all the factors and mechanisms involved in human aggression which present high levels of unpredictability. Conclusion: Authors argue that common programs, regarding the understanding of aggression and of de-escalation strategies, are effective in some way as has already been evidenced anecdotally through literature references, and that de-escalation courses should be useful and should repeated over time with the main aim of empathic communication through practice. Further, literature evidence suggests that simulation scenarios should be preferred to test the effectiveness of a course rather than a paper test or self-assessment quality of the course, but the limit of the artificiality of the scenarios should be overcome.